(3GdaQGSI ajeG hQO aj GdQLGd ef GdSjGSIs ((3eMeO Hf CMeO Hf YHO GdQMef GdMfai GdCMeOi GdTfGhi s)
(3ChdgG (B:s
(3hHYO (B: (3agPg QSGdI ef eUfaGJ GdeJbOejf ai aQGSI GdQLGd s
(3BNQgG (B:s
(3ajeG hLOJ Edi Pdc aQGZkG heG Cdbi GdTGaYi QMdJg Edi CMO ZjQi ef CUMGHg s
(3JCdja HYV GdMceGA hGdeJbOejfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B144 s
Keywords: (3GdaQGSIs